Separate fractions of mRNA from Torpedo electric organ induce chloride channels and acetylcholine receptors in Xenopus oocytes. - Sumikawa, K (1984)
Poly(A)+ mRNA extracted from the electric organ of Torpedo was fractionated by sucrose density gradient centrifugation. After injection into Xenopus oocytes one mRNA fraction induced the appearance of chloride channels in the oocyte membrane. Many of these channels were normally open, and the ensuing chloride current kept the resting potential of injected oocytes close to the chloride equilibrium potential. When the membrane was hyperpolarized, the chloride current was reduced. A separate fraction of mRNA induced the incorporation of acetylcholine receptors into the oocyte membrane. When translated in a cell-free system this fraction directed the synthesis of the alpha, beta, gamma, and delta subunits of the acetylcholine receptor. In contrast, the mRNA fraction that induced the chloride channels caused the synthesis of the delta subunit, a very small amount of alpha, and no detectable beta or gamma subunits. This suggests that the size of the mRNA coding for the chloride channel is similar to the preponderant species of mRNA coding for the delta subunit of the acetylcholine receptor.